alpha-Melanocyte stimulating hormone has beneficial effects on cerulein-induced acute pancreatitis - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
We investigated the effect of alpha-melanocyte stimulating hormone (alpha-MSH) on cerulein induced acute pancreatitis in rats. alpha-MSH treatment (50 mug per rat, intraperitoneally) prior to cerulein reduced the plasma amylase level, pancreatic weight, pancreatic myeloperoxidase activity and the severity of the lesions microscopically. These data suggest that a-MSH has a protective effect on cerulein-induced acute pancreatitis and this effect could be attributed, at least in part, to decreased tissue leukocyte infiltration and thus, to decreased pro-inflammatory cytokine production and/or oxygen- and nitrogen-derived reactive metabolite release. (C) 2004 Elsevier Inc. All nights reserved.
Keywords: pancreatitis; alpha-melanocyte stimulating hormone; neutrophils; rat; NF-KAPPA-B; INFLAMMATION; MSH; MODULATION; ADHESION; INJURY; RAT